WOMAN, MOTHER AND CITIZEN: PERONISM AND ANTIPERONISM IN THE RECOVERY OF THE FEMININE RIGHTS - Perrig, Sara (Revista de Historia Social y de las Mentalidades, 2024)
The intention of this work is to operate  deconstructivamente on the feminine imaginary  of the Peronism in order to show how the  supposed innovation of this one about the  recovery of the women rigths, especially  the right to vote, it is brought down in a  paradoxical speech where the ‘woman’ is  over-determined for the being ‘mother’, or  maternal subject. This paradojal situation,  the need to agree and reject simultaneously  the sexual difference, shows an unsoluble  tension that is re-meant historically and of  which the Peronism cannot escape. Though the  antiperonist women place more than once her  dispute with the latter peronism in terms of the  way as Eva Perón conceptualizes the woman,  it is possible to warn that they also have Only  paradoxes to offer.
Keywords: genre; Eva Perón; antiperonist women